SCIENCE, TECHNOLOGY, ENGINEERING AND MATHEMATICS BASED ON BLENDED LEARNING FOR IMPROVING CRITICAL THINKING ABILITY OF STUDENTS - Ifa Safira; Nur Afni; Mardiana Suyuti; Atmaranie Dewi Purnama; Arham Arham; Abdul Wahid (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2021)
This study aims to develop STEM (learning model Science, Technology, Engineering and Mathematics Based Blended Learning a practical). The problem posed is to produce a practical STEM model in terms of the implementation of learning, learning activities, lecturer responses and student responses. The STEM model was developed by adapting the Plomp’s development model, namely (1) preliminary investigation; (2) design; (3) realization/construction; (4) test, evaluation, and revision and (5) implementation. The model components developed refer to Arend‟s and the model criteria refer to Nieveen‟s. The subjects of this study were ETE students at the Universitas Bosowa. The practicality of the model data was obtained through the instrument implementation of the model, the implementation of learning, as well as learning activities offline and online. The results of this study indicate that the STEM model is declared practical based on the observations of the observer on the implementation of the model, learning management and student learning activities based on the results of the practitioner's assessment of the learning model. Based on the findings, it can be concluded that the STEM Blended Learning model is practical in improving students' critical thinking.Keywords: STEM, blended learning, critical thinking skills